Role of Platelets in the Pathogenicity of Atherosclerosis and Thrombosis in Coronary Heart Diseases - Abubakar Auwal Nasir , Erhabor Osaro , Ibrahim Mohammed , Ahmed Hamidu Marafa , Yakubu * Abdulrahman (Sokoto Journal of Medical Laboratory Science)
Atherosclerosis is a chronic inflammatory process that results in coronary artery disease, peripheral artery disease and in many cases of stroke. It is a disease that involves multiple inflammatory cytokine which is regarded as the primary underlying cause of cardiovascular diseases (CVD). CVD is the leading cause of death in the developed and developing countries like Nigeria. From pathological perspective, the chronic inflammatory condition of atherosclerosis occurs due to interplay between platelets, monocytes, macrophages. Physiologically platelets play a significant role in coagulation and repair of endothelial injury. Pathologically, studies have shown that activated platelets release multiple inflammatory cytokines and chemokines that serve as positive mediators of atherosclerosis. This chemokine is (RANTES, P-selectin and PF-4). Activated platelet release p-selectin that mediate platelet adhesion and rolling to injured endothelial cell, RANTES trigger the recruitment of monocytes into the sub- endothelium and PF4 promote the differentiation of monocytes into macrophages in the intimal layer of the endothelium which engulf ox-LDL to form FOAM cells. Thus, the aim of this review is to understand and describe the role of activated platelets in atherosclerosis as well as therapeutic target of these platelet inflammatory chemokines which is the major mediator of atherosclerosis in human.